The Use of Trusts to Subvert the Law: An Analysis and Critique. (17th January 2021) - Bennett, Mark; Hofri-Winogradow, Adam
Abstract: This article closes a gap in the theory of trust law by supplying a normative account of the use of trusts to avoid and subvert legal norms outside trust law. While the use of trusts to subvert other law has been a major function thereof since the Middle Ages, theorists of trust law have largely steered clear of this function. We evaluate the commonly proffered justifications for the use of trusts to subvert the law, finding that such justifications are not plausible in liberal legal systems, so that the subversive use of trusts should be curtailed. Common law legal systems attempt to curtail this use by anti-subversive norms, but these attempts are far from completely successful. To the extent existing anti-subversive norms cannot be perfected so as to prevent the subversive use of trusts, an approach restricting the available types of trusts may be preferable.